2020
DOI: 10.1016/j.jinf.2020.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of critical & mortal COVID-19 cases: A systematic literature review and meta-analysis

Abstract: Electroencephalogram (EEG) recordings provide a valuable, noninvasive method for measuring human brain activity. This protocol modi es our general protocol for EEG recording (Farrens et al., 2019) for use during the COVID-19 pandemic. It was created with the help of numerous experts, and it speci es a clear set of steps for interacting with research participants, using personal protective equipment (PPE), and disinfecting equipment, all with the goal of reducing the COVID-19 risks for both laboratory personnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

203
1,919
47
111

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,100 publications
(2,427 citation statements)
references
References 27 publications
(24 reference statements)
203
1,919
47
111
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][18][19][20][21][22][23][24][25][26] Only one 17 of the studies reported unadjusted and adjusted ORs using multivariate analysis; after adjusting for confounding by age, maximum temperature at admission, respiratory failure, severe illness, albumin, creatinine, procalcitonin, and C-reactive protein level, the effect of smoking on disease severity increased (unadjusted: OR 12.19, 95% CI 1.76-84.31, p = .011; adjusted: OR 14.29, 95% CI 1.58-25.0, p = .018). Three peer-reviewed meta-analysis papers 6,34,35 on association between smoking and COVID-19 were also based on unadjusted ORs, but with fewer studies included.…”
Section: Limitationsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][18][19][20][21][22][23][24][25][26] Only one 17 of the studies reported unadjusted and adjusted ORs using multivariate analysis; after adjusting for confounding by age, maximum temperature at admission, respiratory failure, severe illness, albumin, creatinine, procalcitonin, and C-reactive protein level, the effect of smoking on disease severity increased (unadjusted: OR 12.19, 95% CI 1.76-84.31, p = .011; adjusted: OR 14.29, 95% CI 1.58-25.0, p = .018). Three peer-reviewed meta-analysis papers 6,34,35 on association between smoking and COVID-19 were also based on unadjusted ORs, but with fewer studies included.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, a nationwide COVID-19 surveillance study conducted in Italy indicated that male mortality rates related to COVID-19 were disproportionately higher than that of female patients with a ratio as much as 4 to 1 (Remuzzi and Remuzzi, 2020). Other systematic reviews performed to characterize clinical features or risk factors for COVID-19, have also identified the sex-specific disparities in disease severity and mortality Zheng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Early data from China and the United States suggest that hypertension appears to be the most prevalent comorbidity among patients admitted with COVID-19 being present in at least 30-49% of them [4,5]. Hypertensive patients who develop COVID-19 are more likely to be admitted to hospital than normotensive individuals [6].…”
mentioning
confidence: 99%